Unit cost analysis of training and deploying paid community health workers in three rural districts of Tanzania. Issue 1 (December 2016) - Tani, Kassimu; Exavery, Amon; Baynes, Colin; Pemba, Senga; Hingora, Ahmed; Manzi, Fatuma; Phillips, James; Kanté, Almamy
Abstract Background Tanzania, like other African countries, faces significant health workforce shortages. With advisory and partnership from Columbia University, the Ifakara Health Institute and the Tanzanian Training Centre for International Health (TTCIH) developed and implemented the Connect Project as a randomized cluster experimental trial of the childhood survival impact of recruiting, training, and deploying of a new cadre of paid community health workers (CHW), named "Wawazesha wa afya ya Jamii" (WAJA). This paper presents an estimation of the cost of training and deploying WAJA in three rural districts of Tanzania. Methods Costing data were collected by tracking project activity expenditure records and conducting in-depth interviews of TTCIH staff who have led the training and deployment of WAJA, as well as their counterparts at Public Clinical Training Centres who have responsibility for scaling up the WAJA training program. The trial is registered with the International Standard Randomized Controlled Trial Register number (ISRCTN96819844 ). Results The Connect training cost was US$ 2, 489.3 per WAJA, of which 40.1 % was for meals, 20.2 % for accommodation 10.2 % for tuition fees and the remaining 29.5 % for other costs including instruction and training facilities and field allowance. A comparable training program estimated unit cost for scaling-up this training via regional/district clinical training centres would be US$ 833.5 per WAJA. Of this unit cost, 50.3 % would involve the cost of meals, 27.4 % training fees, 13.7 % for field allowances, 9 % for accommodation and medical insurance. The annual running cost of WAJA in a village will cost US$ 1.16 per capita. Conclusion Costs estimated by this study are likely to be sustainable on a large scale, particularly if existing regional/district institutions are utilized for this program.